2017
DOI: 10.1002/jtr.2109
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and Experiences of Whitewater Rafting Tourists on the Ocoee River, USA

Abstract: This study explored the relationships that adventure motivations have with adventure experiences (i.e. emotional response and place attachment) and behavioral outcomes (i.e. revisit intention and word-of-mouth). Based on 690 surveys collected from whitewater rafters at the Ocoee River in Tennessee, structural equation modeling revealed that thrill and nature motivations led to a positive affective response towards the adventure activity, which led to an attachment to the adventure destination and positive beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 82 publications
0
20
0
1
Order By: Relevance
“…A recent study of 690 surveys of individuals taking part in these excursions have indicated that thrill and nature motivations lead to a positive affective response towards whitewater rafting and kayaking, which leads to an attachment to the adventure destination and positive behavioral outcomes. The study also revealed that perceived risk is a significant moderator between thrill and this affective response (4). It would stand to reason that by offering the opportunity to traverse more difficult rapids, it would increase the individual's experience and increase the chances to become a whitewater enthusiast, specifically through those companies offering a greater “thrill value” with less strict criteria.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study of 690 surveys of individuals taking part in these excursions have indicated that thrill and nature motivations lead to a positive affective response towards whitewater rafting and kayaking, which leads to an attachment to the adventure destination and positive behavioral outcomes. The study also revealed that perceived risk is a significant moderator between thrill and this affective response (4). It would stand to reason that by offering the opportunity to traverse more difficult rapids, it would increase the individual's experience and increase the chances to become a whitewater enthusiast, specifically through those companies offering a greater “thrill value” with less strict criteria.…”
Section: Discussionmentioning
confidence: 91%
“…Penelitian-penelitian terdahulu telah banyak diakukan terkait dengan pengalaman wisatwan seperti (Amoa et al, 2017;Beckman et al, 2017;Chen dan Rahman, 2018;Roza., 2017), begitu juga terkait dengan nilai yang dihubungkan dengan loyalitas (Kyoungjin dan Graham, 2012;Ali et al, 2018;Castellanos-Verdugo et al 2016;Chen dan Chen, 2010;Chen dan Rahman, 2018;Prebensen et al, Woo, 2013;Sthapit dan Coudounaris, 2018), namun penelitian lain menunjukkan hasil berbeda, dengan menggunakan variabel multi dimensional baik brand experience maupun brand loyalty, diketahui brand experience (sensory experience, behavioral expereince) tidak berpengaruh terhadap brand loyalty (WOM, repurchase intention). Penelitian lain oleh Quan et al (2020), menunjukkan bahwa E-brand experience tidak berpengaruh terhadap E-brand loyalty, sehingga penelitian hubungan antara brand experience terhadap brand loyalty masih terdapat ketidak jelasan hubungan tersebut.…”
Section: Gambar 1 Portofolio Produk Destinasi Indonesiaunclassified
“…should be researched (Allan, 2016;Guzel, 2014). Moreover, in the literature review, it is seen that the relevant literature has various adventure experience-based studies which are focused on mostly on diving, whitewater rafting, river, scuba divers, sea kayakers, canoeing (Beckman et. al, 2017;Cheng and Tsaur, 2012;Varley, 2011;Dimmock, 2009;Schreyer and Roggenbuck, 1978).…”
Section: Tourism Experience and 4e Experience Modelmentioning
confidence: 99%